Model Pembelajaran Aktivitas Kebugaran Jasmani melalui Permainan Puzzle Run - KHAMAMI, KHAMAMI; Sudarmono, Martin (Universitas Negeri Semarang, 2023)
The aim of the researcher through this research is to produce game media products to facilitate physical fitness learning in fourth grade elementary schools. This research is a research and development (R&D). The results of the initial product expert validation obtained an average (83.3%) very good. With the revision, the safety of students and equipment was adjusted to the characteristics of elementary school students. The results of small-scale trials obtained on average (83.61%) were very good. The expert's revision results stated that it was feasible to use. The results of large-scale trials obtained on average (89.38%) are very good. Based on the results of the research analysis, the puzzle run game media can be used as a medium for learning physical fitness activities in elementary schools. suggestions for physical education teachers, it is hoped that they can use this media for learning physical fitness activities according to the media use book so that they can help students become more active and enthusiastic about participating in physical education learning at school.